Pengaruh Perilaku Konsumtif, Pemberian Reward, Redibilitas Platform Terhadap Keputusan Penggunaan E-Wallet Pada Transaksi E-Commerce Dengan Kemudahan Penggunaan Sebagai Variabel Moderating (Studi Kasus : Mahasiswa FEBI UIN Sumatera Utara) - Wahyu Sahara Ramadhana Manurung; Nur Ahmadi Bi Rahmani; Nuri Aslami (Universitas Labuhanbatu, 2023)
The purpose of this research is to find out whether consumptive behavior, giving reward, credibility platform effect on decisions usage e-wallet on transactions e-commerce with ease of use as a variable moderating. This type of research is quantitative. Data collection techniques using a questionnaire (questionnaire). The sampling technique of this study uses Purposive Sampling with a total of 98 respondents. Data analysis technique using test Moderated Regression Analysis with the help of IBM SPSS application Statistic 26.0. The research results show: first, consumptive behavior has a significant effect on the decision to use e-wallet LinkAja with a significance of 0.001<α0.05.Second, gift reward no significant effect on the decision to use e-wallet LinkAja with a significance of 0.199>α0.05.Third, credibility platform significant effect on the decision to use e-wallet LinkAja with a significance of 0.012<α0.05.Fourth, Consumptive Behavior, Giving Reward, Credibility Platform simultaneously significant effect on the decision to use e-wallet LinkAja with a significance of 0.000<α0.05.Fifth. Ease of use is able to moderate the effect of consumptive behavior on usage decisions-wallet LinkAja with a significance of 0.024<α0.05. Sixth, ease of use was unable to moderate the effect of administration reward on usage decisions-wallet LinkAja. with a significance of 0.085<α0.05. Seventh, ease of use is able to moderate the influence of the credibility platform on usage decisions-wallet LinkAja with a significance of 0.024<α0.05.